Penggunaan Metode dan Teknik Penerjemahan Pada Lirik Lagu "Mungkin Nanti" Karya Ariel NOAH ke dalam Bahasa Jepang Oleh Hiroaki Kato - Ros Diana; Ana Natalia (KIRYOKU, 2022)
This research is entitled "Analysis of Translation Methods and Techniques on the Song Lyrics of "Mungkin Nanti" by Ariel NOAH into Japanese by Hiroaki Kato". This study aims to find out the use of translation methods and translation techniques applied to the lyrics of Ariel NOAH's song " Mungkin Nanti" which was translated into Japanese by Hiroaki Kato. The theory used in this translation method is Newmark, and the translation technique used is the theory of Molina and Albir. This research methodology uses descriptive analysis with a qualitative approach, in other words, that is to describe or describe the data that has been obtained. This study uses data analysis techniques using the agih method and the direct element technique (BUL). Based on the results of the analysis can be obtained 18 data translation methods and techniques. According to the 8 translation methods proposed by Newmark, it was found that there were 4 translation methods used in the lyrics of the song " Mungkin Nanti",1 data literal translation, 2 data Semantic translations, 5 data free translations, and 10 data Communicative translations, and then the data were analyzed to determine the translation technique from Molina and Albir, there were 4 translation techniques used, 2 data common equivalents, 4 data modulations, 6 data reductions, and 6 data transpositions.